Pengaruh Pengendalian Internal, Literasi Pajak Terhadap Keberlanjutan UMKM Kabupaten Kubu Raya Dimoderasi Oleh Digitalisasi - Chairunisa; Risal; Afif, Ali (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
MSMEs are profitable companies that are either sole proprietorships or owned by individuals. However, many MSMEs in Kubu Raya are not yet sustainability-oriented, as they are still simply run and run by their owners. Internal control, which should make business operations more effective and efficient, has proven to be inadequate. However, as demonstrated by the less than ideal tax collection, tax literacy which ought to be a motivator for timely tax payment and reporting has not been entirely achieved. This research aims to examine how digitization functions as a moderating factor in Kubu Raya Regency, as well as Internal control and tax literacy's effects on MSMEs' sustainability. 99 respondents in Kubu Raya Regency were selected using a straightforward random sample procedure in a quantitative study. With the aid of Multiple SPSS version 25 was utilized to analyze the data using linear regression, descriptive statistics, data quality testing (validity and reliability), traditional assumption testing, and Moderated Regression Analysis (MRA). The sustainability of MSMEs is significantly impacted by internal control. Furthermore, tax literacy significantly improves MSMEs' capacity to survive. Additionally, the impact of internal control on MSMEs' sustainability can be mitigated via digitization. With the aid of digitization, internal control and tax literacy contribute significantly to Kubu Raya Regency's MSMEs' sustainability.